(untitled) (Journal of the College of Basic Education, 2022)
Globalization is considered one of the most important developments in the contemporary world and its dominant and controlling preparation in various economic fields and sayings and religious through the resulting intellectual and cultural control that contributed to the duality of thought and the Arab personality. Globalization affected the entire disciplines in terms of interior design as a result of the tremendous scientific and technological progress that resulted in the emergence of Modern materials and techniques in design and implementation have contributed greatly to the design transformations that have emerged in contemporary building designs that have emerged in a western style far from our Arab culture, and this transformation has affected Arab mosque buildings that have always been based on several fixed traditions with historical, ideological and heritage considerations stemming from the feature of Arab society, have imposed on globalization the global pattern of its references and its ideas, The structure and trends of the interior design are affected by intellectual influences that may be internal stemming from the development of society or external as a result of the act of globalization and what it leads to from thought that may find acceptance or rejection in society. As a result, design thought collided between the acquisition of the authentic culture of society and what was expropriated from other cultures as a result of globalization, And within that appeared intellectual transformations that reflected the style of interior design in Arab societies, affecting the form and design ideas of religious mosques to be a fertile field for dialogue and criticism, especially since globalization has collided with the trends of ethics and values rooted in the Arab community, which carries privacy, leading to problems related to local history and heritage, After what globalization has endeavored to lift societal barriers and restrictions and open borders and related personal and religious freedoms, From here we find a scientific justification for dealing with the subject of the current study, as the research problem in it can be summed up by the following: "The lack of defining the dynamism of globalization and its transformations within the visions of the interior designer". The research Include in the Introduction on methodological framework and with identifying the most important terms, then the theoretical framework that in turn included two topics first: (The study of dynamism and the act of globalization in interior design), and the second: (transformations of intellectual globalization in the design of contemporary mosques), followed by research procedures supported by some design models that were analyzed and come up with the results of the research that resulted from the process of analysis and then the conclusions.